1960
DOI: 10.1111/j.1748-1716.1960.tb01854.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Histamine Release in Anaphylactic Reaction in Guinea Pig and Rat

Abstract: Chakravarty, N. The mchanism of histamine release in anaphylactic reaction in guinea pig and rat. The mechanism of histamine release was studied in anaphylactic reaction in vitro in tissues from guinea pig and rat; it was compared, in rat, with histamine release induced by compound 48/80. The observations suggest that histamine release in both species is mediated by the activation of an enzyme system probably with essential sulphydryl and amino groups. Histamine release in anaphylaxis and that induced by compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0

Year Published

1962
1962
1985
1985

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…Vascular tissue was first shown to release SRS-A more than 20 years ago (Brocklehurst, 1960;Chakravarty, 1960), and more recently it has been demonstrated that large peripheral blood vessels obtained from a variety of species, including the dog, possess the capacity to synthesize and release leukotriene-like substances Wolbling et al, 1983;Dembinska-Kiec et al, 1984). Although the formation of leukotrienes in vascular smooth muscle has not been unequivocally demonstrated, these derivatives stimulate vascular smooth muscle and may participate in vasomotor control mechanisms.…”
mentioning
confidence: 99%
“…Vascular tissue was first shown to release SRS-A more than 20 years ago (Brocklehurst, 1960;Chakravarty, 1960), and more recently it has been demonstrated that large peripheral blood vessels obtained from a variety of species, including the dog, possess the capacity to synthesize and release leukotriene-like substances Wolbling et al, 1983;Dembinska-Kiec et al, 1984). Although the formation of leukotrienes in vascular smooth muscle has not been unequivocally demonstrated, these derivatives stimulate vascular smooth muscle and may participate in vasomotor control mechanisms.…”
mentioning
confidence: 99%
“…Histamine release from guinea-pig lung induced by the antigen-antibody reaction is dependent on calcium (Mongar & Schild, 1958;Chakravarty, 1960) and the anaphylactic histamine release from rat mast cells is maximal at a calcium concentration of 1 to 2 x 10-' mol/l (Foreman & Mongar, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Anaphylactic histamine release from guinea-pig lung and disruption of rat mast cell due to antigen is dependent on the incubation temperature (Mongar & Schild, 1957;Chakravarty, 1960;Hogberg & Uvniis, 1960). Histamine release from guinea-pig lung induced by the antigen-antibody reaction is dependent on calcium (Mongar & Schild, 1958;Chakravarty, 1960) and the anaphylactic histamine release from rat mast cells is maximal at a calcium concentration of 1 to 2 x 10-' mol/l (Foreman & Mongar, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…The anaphylactic histamine release from most organs of guinea pigs ranges between 25 and 33% of total organ histamine when tested in vitro without aminoguanidine protection [5,6]. The liver holds a unique posi- For calculation of recovery, the Ipasma histamine levels determined after the histamine injection were subtracted by 0.05 /(g/ml, i.e., the mean histamine level determined in the liver blood plasma of 3 animals not injected with histamine (0.05 ±0.01 //g/ml).…”
Section: Discussionmentioning
confidence: 99%